Carbon-Ion Radiotherapy for Oral Non-Squamous Cell Carcinoma: Clinical and Radiophysical Perspectives for Indonesia - Ringgit Purbowati; Raditya Faradina (Journal of Energy, Material, and Instrumentation Technology, 2026)
Oral non-squamous cell carcinoma (non-SCC) represents a radioresistant malignancy that often responds poorly to conventional X-ray radiotherapy. This resistance creates major clinical challenges, especially in resource-limited settings such as Indonesia. Carbon-ion radiotherapy (C-ion RT) has emerged as an advanced treatment modality that offers superior dose distribution and higher biological effectiveness, making it particularly promising for tumors that are refractory to photon therapy. A systematic narrative review was conducted following the PRISMA 2020 framework. Literature searches in PubMed, Scopus, and ScienceDirect (January 2013-June 2024) used the terms "carbon-ion radiotherapy," "oral cancer," "non-squamous cell carcinoma," "clinical outcome," and "toxicity." Studies reporting quantitative data on treatment outcomes were included and analyzed descriptively from both clinical and medical physics perspectives. Thirty-two eligible studies were reviewed, including data from Japan, Germany, and Italy. Across these cohorts, C-ion RT achieved a mean 5-year local control rate of 78.8% and an overall survival rate of 58.3%, outperforming conventional X-ray radiotherapy and demonstrating superiority over proton therapy in biological effectiveness (RBE about 2-3). The dominant acute toxicity was mild-to-moderate oral mucositis (about 28%, grade 1-2), while late osteoradionecrosis occurred in 10-14% of cases but was largely manageable with conservative care. C-ion RT offers a unique combination of physical precision and biological potency that makes it highly effective for radioresistant oral cancers. For Indonesia, its gradual implementation, supported by international collaboration, workforce training, and national policy integration, could enhance cancer treatment capacity and stimulate innovation in medical physics and radiotherapy technology. This review also discusses the strategic readiness for integrating C-ion RT into Indonesia's healthcare system.